Analisis Keuntungan dan Skala Produksi Usahatani Bawang Merah Pada Lahan Sawah Irigasi di Kecamatan Simpang Tiga Kabupaten Pidie - Syafiqur Rahman; M. Nasir Ismail; Teuku Fadhla; Syarifuddin Syarifuddin (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The aim of the research is to find out how big the profits of shallot farmers' farming in irrigated rice fields are and to find out the scale of production of shallot farming in Simpang Tiga District. The research methodology is